VD_FINDINFO HC / 2012 / 338 vom 25. Mai 2012 - VD Tribunal cantonal (2012)
EXÉCUTION FORCÉE, EXPULSION DE LOCATAIRE | 309 let. a CPC (CH), 319 let. a CPC (CH), 320 let. a CPC (CH), 320 let. b CPC (CH), 322 al. 1 CPC (CH), 326 CPC (CH), 339 al. 2 CPC (CH), 341 CPC (CH)